Policy Perspective on Continuous Professional Development: Enhancing Teaching and Learning through Inclusive Practices and Zero Tolerance towards Discrimination (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The Equality Act 2010 is the legislation surrounding the topics of equality and diversity. Academic staff has a responsibility to deliver teaching and learning that meets the required standards mentioned above. This could mean paying attention to the needs of the students, ensuring you consider inclusivity and accessibility. Additionally, make it clear to students that you have a zero tolerance policy toward discrimination by letting them know the ways you expect them to interact with each other, and deal promptly and efficiently with inappropriate behaviour if it ever occurs. By finding opportunities within your teaching to prompt students to work collaboratively in diverse groups through creative and respectful techniques, you can add value to the learning experience for everyone.